The Problem of Maintaining the Volume of Bone Tissue After Tooth Extraction and Ways to Solve it (Eurasian Medical Research Periodical, 2022)
Dental implantation of teeth is a modern technology that helps patients return to a full life after the psychological and physical discomfort of losing teeth. These days, dental implantation is a revolutionary method of restoring damaged or completely missing (after extraction or loss) teeth. It has been successfully used by dental clinics around the world for more than two decades. Dental implantation has replaced the more outdated method of prosthetics, when adjacent teeth were killed, between them the doctor installed bridges, and then crowns. Using implantation as a way to restore teeth and their function, the remaining neighboring teeth are not damaged at all (Vinichenko O.Yu., 2016; Zhdanov E.V., 2016). Direct implant placement immediately after tooth extraction is a fairly common and effective procedure. Although the percentage of implantation success both when using the algorithms of one-stage and delayed installation is almost identical, however, according to the literature, when carrying out the loading procedure immediately after extraction, it is possible to preserve the hard and soft tissues of the buccal wall of the alveolar socket and prevent their progressive loss by at least 1 mm, especially in cases of a thin biotype of the vestibular cortical wall (Vishnyakov V.V. 2010; Kulakov A.A. 2010; Koshel V.I. 2014; Sirak S.V. 2014).